Delte type dependencie in Monad record for escape implicit type conflict
author Yasutaka Higa Mon, 26 Jan 2015 14:08:46 +0900 9c62373bd474 ebd0d6e2772c
line wrap: on
line source
```
open import Level
open import Relation.Binary.PropositionalEquality
open ≡-Reasoning

open import basic
open import delta
open import delta.functor
open import deltaM
open import deltaM.functor
open import laws

open Functor
open NaturalTransformation

postulate deltaM-mu-is-natural-transformation : {l : Level} {A : Set l}
{M : {l' : Level} -> Set l' -> Set l'} ->
{functorM :  {l' : Level} -> Functor {l'}  M}
{monadM   : {l' : Level} -> Monad {l'} M (functorM ) } ->
NaturalTransformation (\A -> DeltaM M (DeltaM M A)) (\A -> DeltaM M A)
{deltaM-fmap ∙ deltaM-fmap} {deltaM-fmap {l}}
(deltaM-mu {_} {_} {M} {functorM} {monadM})

headDeltaM-commute : {l : Level} {A B : Set l}
{M : {l' : Level} -> Set l' -> Set l'} ->
{functorM :  {l' : Level}  -> Functor {l'}  M} ->
{monadM   : {l' : Level} -> Monad {l'} M (functorM ) } ->
(f : A -> B) -> (x : DeltaM M {functorM} {monadM} A) ->
headDeltaM-commute f (deltaM (mono x))    = refl
headDeltaM-commute f (deltaM (delta x d)) = refl

headDeltaM-is-natural-transformation : {l : Level} {A : Set l}
{M : {l' : Level} -> Set l' -> Set l'} ->
{functorM :  {l' : Level} -> Functor {l'} M}
{monadM   : {l' : Level} -> Monad {l'} M functorM } ->
NaturalTransformation {l} (\A -> DeltaM M {functorM} {monadM} A) M
{\f d → deltaM (mono (headDeltaM (deltaM-fmap f d)))} {fmap functorM} headDeltaM
--                                                                      {deltaM-fmap} {fmap (functorM {l} {A})} headDeltaM

deltaM-right-unity-law : {l : Level} {A : Set l}
{M : {l' : Level} -> Set l' -> Set l'}
(functorM : {l' : Level} -> Functor {l'} M)
(d : DeltaM M {functorM} {monadM} A) ->
(deltaM-mu ∙ deltaM-eta) d ≡ id d
deltaM-right-unity-law {l} {A} {M} functorM monadM (deltaM (mono x)) = begin
(deltaM-mu ∙ deltaM-eta) (deltaM (mono x))                ≡⟨ refl ⟩
deltaM-mu (deltaM-eta (deltaM (mono x)))                  ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (eta monadM (deltaM (mono x)))))  ≡⟨ refl ⟩
deltaM (mono (mu monadM (fmap functorM (headDeltaM {l} {A} {M}) (eta monadM (deltaM (mono x))))))  ≡⟨ refl ⟩
≡⟨ cong (\de -> deltaM (mono (mu monadM de))) (sym (eta-is-nt monadM headDeltaM (deltaM (mono x)))) ⟩
≡⟨ refl ⟩
≡⟨ cong (\x -> deltaM (mono x)) (sym (right-unity-law monadM x)) ⟩
deltaM (mono x)
≡⟨ refl ⟩
id (deltaM (mono x))
∎
deltaM-right-unity-law {l} {A} {M} functorM monadM (deltaM (delta x d)) = begin
(deltaM-mu ∙ deltaM-eta) (deltaM (delta x d))  ≡⟨ refl ⟩
deltaM-mu (deltaM-eta (deltaM (delta x d)))    ≡⟨ refl ⟩
deltaM-mu (deltaM (mono (eta monadM (deltaM (delta x d)))))    ≡⟨ refl ⟩
≡⟨ cong (\de -> deltaM (mono (mu monadM de))) (sym (eta-is-nt monadM headDeltaM (deltaM (delta x d)))) ⟩
≡⟨ refl ⟩
≡⟨ {!!} ⟩
id (deltaM (delta x d))
∎

{-
deltaM-association-law : {l : Level} {A : Set l}
{M : {l' : Level} -> Set l' -> Set l'}
(functorM : {l' : Level}  -> Functor {l'} M)
(monadM   : {l' : Level} {A : Set l'} -> Monad {l'} {A} M functorM)
-> (d : DeltaM M (DeltaM M (DeltaM M {functorM} {monadM} A)))
-> ((deltaM-mu ∙ (deltaM-fmap deltaM-mu)) d) ≡ ((deltaM-mu ∙ deltaM-mu) d)
deltaM-association-law functorM monadM (deltaM (mono x))    = begin
(deltaM-mu ∙ deltaM-fmap deltaM-mu) (deltaM (mono x))                           ≡⟨ refl ⟩
deltaM-mu (deltaM-fmap deltaM-mu (deltaM (mono x)))                             ≡⟨ refl ⟩
deltaM-mu (deltaM (delta-fmap (fmap functorM deltaM-mu) (mono x)))              ≡⟨ {!!} ⟩
deltaM-mu (deltaM-mu (deltaM (mono x)))                                         ≡⟨ refl ⟩
deltaM-mu (deltaM-mu (deltaM (mono x)))                                         ≡⟨ refl ⟩
(deltaM-mu ∙ deltaM-mu) (deltaM (mono x))                                       ∎
deltaM-association-law functorM monadM (deltaM (delta x d)) = {!!}
-}

{-

nya : {l : Level} {A B C : Set l} ->
{M : {l' : Level} -> Set l' -> Set l'}
{functorM : {l' : Level} -> Functor {l'} M }
{monadM : {l' : Level} {A : Set l'} -> Monad {l'} {A} M functorM}
(m : DeltaM M {functorM} {monadM}  A)  -> (f : A -> (DeltaM M {functorM} {monadM} B)) -> (g : B -> (DeltaM M C)) ->
(x : M A) ->
(deltaM (fmap delta-is-functor (\x -> bind {l} {A} monadM x (headDeltaM ∙ (\x -> deltaM-bind (f x) g))) (mono x))) ≡
(deltaM-bind (deltaM (fmap delta-is-functor (\x -> (bind {l} {A} monadM x (headDeltaM ∙ f))) (mono x))) g)
nya = {!!}

deltaM-monad-law-h-3 : {l : Level} {A B C : Set l} ->
{M : {l' : Level} -> Set l' -> Set l'}
{functorM : {l' : Level} -> Functor {l'} M }
{monadM : {l' : Level} {A : Set l'} -> Monad {l'} {A} M functorM}
(m : DeltaM M {functorM} {monadM}  A)  -> (f : A -> (DeltaM M  B)) -> (g : B -> (DeltaM M C)) ->
(deltaM-bind m (\x -> deltaM-bind (f x) g)) ≡ (deltaM-bind (deltaM-bind m f) g)
{-
deltaM-monad-law-h-3 {l} {A} {B} {C} {M} {functorM} {monadM} (deltaM (mono x)) f g    = begin
(deltaM-bind (deltaM (mono x)) (\x -> deltaM-bind (f x) g))                         ≡⟨ refl ⟩

(deltaM (mono (bind {l} {A} monadM x (headDeltaM ∙ (\x -> deltaM-bind (f x) g)))))  ≡⟨ {!!} ⟩
(deltaM-bind (deltaM (fmap delta-is-functor (\x -> (bind {l} {A} monadM x (headDeltaM ∙ f))) (mono x))) g) ≡⟨ refl ⟩
(deltaM-bind (deltaM (mono (bind {l} {A} monadM x (headDeltaM ∙ f)))) g) ≡⟨ refl ⟩
(deltaM-bind (deltaM-bind (deltaM (mono x)) f) g) ∎
-}

deltaM-monad-law-h-3 {l} {A} {B} {C} {M} {functorM} {monadM} (deltaM (mono x)) f g    = begin
(deltaM-bind (deltaM (mono x)) (\x -> deltaM-bind (f x) g))                         ≡⟨ refl ⟩
(deltaM (mono (bind {l} {A} monadM x (headDeltaM ∙ (\x -> deltaM-bind (f x) g)))))  ≡⟨ {!!} ⟩
--  (deltaM (fmap delta-is-functor (\x -> bind {l} {A} monadM x (headDeltaM ∙ (\x -> deltaM-bind (f x) g))) (mono x))) ≡⟨ {!!} ⟩